Atomistic insights into the order–disorder transition in Cu2ZnSnS4 solar cells from Monte Carlo simulations. Issue 1 (5th December 2018) - Wallace, Suzanne K.; Frost, Jarvist Moore; Walsh, Aron
Abstract : Kesterite-structured Cu2 ZnSnS4 (CZTS) is an earth-abundant and non-toxic semiconductor that is being studied for use as the absorber layer in thin-film solar cells. Abstract : Kesterite-structured Cu2 ZnSnS4 (CZTS) is an earth-abundant and non-toxic semiconductor that is being studied for use as the absorber layer in thin-film solar cells. Currently, the power-conversion efficiencies of this technology fall short of the requirements for commercialisation. Disorder in the Cu–Zn sub-lattice has been observed and is proposed as one explanation for the shortcomings of CZTS solar cells. Cation site disorder averaged over a macroscopic sample does not provide insights into the microscopic cation distribution that will interact with photogenerated electrons and holes. To provide atomistic insight into Cu/Zn disorder, we have developed a Monte Carlo (MC) model based on pairwise electrostatic interactions. Substitutional disorder amongst Cu and Zn ions in Cu–Zn (001) planes on the 2c and 2d Wyckoff sites – 2D disorder – has been proposed as the dominant form of Cu/Zn disorder in near-stoichiometric crystals. We use our model to study the Cu/Zn order–disorder transition in 2D but also allow Zn to substitute onto the Cu 2a site – 3D disorder – including Cu–Sn (001) planes. We find that defects are less concentrated in Cu–Sn (001) planes but that Zn ions readily substitute onto the Cu 2a site and that the critical temperature is lowered for 3D disorder.